Crustal structure, gravity anomalies and subsidence history of the Parnaíba cratonic basin, Northeast Brazil - Tozer, B (2017)
Cratonic basins cover more than 10% of Earth's continental surface area, yet their origin remains enigmatic. In this thesis a suite of new and legacy geophysical and geological data are integrated to constrain the origin of the Parnaíba basin, a cratonic basin in Northeast Brazil. These data include a 1400 km long, deep (20 s two-way travel time) seismic reflection profile, five +/- 110 km offset wide-angle split-spread receiver gathers, gravity anomaly, and well data. In the centre of the basin, the depth to pre-Paleozoic basement is ∼ 3.3 km, a zone of midcrustal reflectivity (MCR) can be traced laterally for ∼ 250 km at depths between 17-25 km and Moho depth is ∼ 42 +/- 2 km. Gravity and P-wave modelling suggests that the MCR represents the upper surface of a high density (2985 kg m3) and Vp (6.7–7.0 km s-1) lower crustal body, likely of magmatic origin. Backstripping of well data shows a concave up decreasing tectonic subsidence, similar in form to that commonly observed in rift-type basins. It is shown, however, that the seismic and gravity data are inconsistent with an extensional origin. It is shown that an intrusive body in the lower crust that has loaded and flexed the surface of the crust, combined with sediment loading, provides a satisfactory fit to the observed gravity anomaly, sediment thickness and basin shape. A buried load model is also consistent with seismic data, which suggest that the Moho is as deep or deeper beneath the basin centre than its flanks and accounts for at least part of the tectonic subsidence through a viscoelastic stress relaxation that occurs in the lithosphere following load emplacement. Comparative analysis of the Michigan and Congo basins shows gravity data from these basins is also consistent with a lower crustal mass excess, while subsidence analysis shows viscoelastic stress relaxation may also contribute to their early subsidence histories. However, unlike Parnaíba, both of these basins appear to have been subjected to secondary tectonic processes that obscure the primary 'cratonic basin' subsidence signals. Parnaíba basin, therefore, offers an excellent record for the investigation of cratonic basin formation.